Statutory valuations - Baum, Andrew, 1953- (International Thomson Business, 1997)
Commercial property. Residential property 1: the Rent acts. Residential property 2: leasehold reform for houses. Residential property 3: leasehold reform for flats. Compulsory purchase compensation 1, 2, 3, 4.